Axonal degeneration and inflammation in acute optic neuritis. Issue 8 (16th July 2004) - Petzold, A; Rejdak, K; Plant, G T
Abstract : Aims: To investigate whether plasma biomarkers for axonal injury and inflammation are related to loss and recovery of visual function in acute optic neuritis (ON). Methods: Eighteen patients with ON and 14 controls were investigated in a longitudinal, prospective study. Plasma phosphorylated neurofilament heavy chain (NfH SMI35 ; a surrogate marker of axonal injury), nitric oxide metabolites (NOx), and citrulline (surrogate markers of inflammation) were measured. Results: Patients with ON had higher median plasma NfH SMI 35 values than controls (0.17 versus 0.005 ng/ml; p < 0.05) and higher NOx values (49 versus 35.5μM; p < 0.001). Plasma NfH SMI35 values correlated inversely with visual acuity at presentation ( R  =  −0.67; p  =  0.01). NfH SMI35 was higher in patients with poor recovery of visual acuity than in those with good recovery (0.25 ng/ml versus 0.09 ng/ml; p < 0.05). Three of four patients with high NfH SMI35 and high NOx values experienced a poor recovery as opposed to only one of five with high NOx but normal NfH SMI35 values. Conclusions: NfH SMI35, a surrogate marker for axonal damage, is a prognostic indicator and should be considered in the design of neuroprotective treatment strategies.